Sharia-Compliant Transformation of Village-Owned Enterprises: Accountability, Implementation, and Regulatory Readiness in West Nusa Tenggara - Asmawati, Asmawati; Fahrudin, Fahrudin (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the factors influencing the success of the transformation of Village-Owned Enterprises (BUMDes) into a sharia-compliant model in West Nusa Tenggara (NTB) province. Employing a Mixed Methods approach with a Sequential Exploratory design, this research integrates both qualitative and quantitative studies. The qualitative phase involved in-depth interviews with 7 key informants from BUMDes